2020
DOI: 10.1136/practneurol-2020-002586
|View full text |Cite
|
Sign up to set email alerts
|

Bartonella neuroretinitis (cat-scratch disease)

Abstract: We report a patient with cat-scratch disease presenting with meningitis and neuroretinitis. This condition, caused by Bartonella henselae, has a worldwide distribution and is among the most common infective causes of neuroretinitis. Bartonella neuroretinitis is a rare but under-recognised mimic of optic neuritis; it should be suspected in a patient with an infective prodrome whose fundus shows optic disc oedema and a macular star. A low-positive initial serological test for Bartonella henselae does not exclude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 2 publications
0
15
0
1
Order By: Relevance
“…The patient's mother had a history of breeding cats, which was mentioned in another day interview, and the antibody against Bartonella henselae was positive at a later date, resulting in the definitive diagnosis of optic retinitis associated with CSD. The frequency of optic neuroretinitis in CSD is 1–2%, but according to Yap et al [ 6 ], CSD is one of the most common infectious causes of infectious optic neuroretinitis.…”
Section: Discussionmentioning
confidence: 99%
“…The patient's mother had a history of breeding cats, which was mentioned in another day interview, and the antibody against Bartonella henselae was positive at a later date, resulting in the definitive diagnosis of optic retinitis associated with CSD. The frequency of optic neuroretinitis in CSD is 1–2%, but according to Yap et al [ 6 ], CSD is one of the most common infectious causes of infectious optic neuroretinitis.…”
Section: Discussionmentioning
confidence: 99%
“…Yep et al [ 127 ] reported on the case of a young woman presenting with meningitis and neuroretinitis who had fever, sweating, a left frontal headache, hazy vision, and painful left-eye movements for five days. A central scotoma decreased color vision, and enlargement of the optic disc and macula were seen in the left eye.…”
Section: Neurologic Manifestationsmentioning
confidence: 99%
“…При поступлении пациент был обследован на бартонеллез, тест оказался отрицательным. Однако при повторном проведении анализа был выявлен диагностический титр антител к Bartonella henselae [13].…”
Section: материалы и методыunclassified